Developing Cost-Effective and High-Speed 40 Gbps FSO Systems Incorporating Wavelength and Spatial Diversity Techniques - Satish Kumar Modalavalasa; Rajan Miglani; Sushank Chaudhary; Faisel Tubbal; Faisel Tubbal; Raad Raad (Frontiers in Physics, 2021)
Free-space optical (FSO) communication systems are being anticipated to offer promising alternatives to existing radio networks in delivering high-speed data access to end-users. Ease of installation, robust features, and cost-effective operation have been the hallmark of FSO systems, and these features will play an obvious role in deciding the ways in which futuristic smart communication models will operate. Despite these arrays of features, FSO links suffer severe performance degradation due to channel-induced impairments caused by atmospheric effects such as rain, haze, and fog. In this work, we have investigated and compared the performance of 40 Gbps FSO links for different channel conditions ranging from clear weather to severe attenuation by incorporating spatial and wavelength diversity as performance booster techniques. The use of an erbium-doped fiber amplifier (EDFA) with FSO links has also been proposed here. Using performance metrics like bit error rate (BER) and eye patterns, it has been found that the use of EDFA not only helps in compensating for the link losses but also aids in realizing an all-optical processing based last-mile access system. The proposed FSO system will be capable of bridging the existing backbone fiber networks with end-users with minimal changes to the existing hardware regime, thereby proving to be extremely cost-effective in sharp contrast to radio-frequency generations which require major infrastructure overhaul.